Highly efficient CO2 adsorption by nitrogen-doped porous carbons synthesized with low-temperature sodium amide activation. (April 2018) - Wang, Liwei; Rao, Linli; Xia, Binbin; Wang, Linlin; Yue, Limin; Liang, Yuqing; DaCosta, Herbert; Hu, Xin
Abstract: This work provides a simple and cost-effective way to synthesize carbonaceous sorbents with superior CO2 capture performance under ambient conditions. Using a carbonized commercial phenolic resin as carbon precursor and NaNH2 as both activation agent and nitridation reagent, nitrogen-doped porous carbons were synthesized by a single-step reaction at 400-500 °C. The resulting carbons were highly microporous with large amounts of nitrogen content and CO2 uptake capacities up to 4.64 and 7.13 mmol/g, at atmospheric pressure and, respectively, 25 °C and 0 °C. A systematic study showed that the synergetic effect of narrow microporosity and nitrogen content determines the sorbents' CO2 capture capability. In addition, these phenolic-resin-derived porous carbons demonstrate excellent recyclability, stability, and dynamic CO2 capture capacity, as well as reasonable heat of adsorption and CO2 /N2 selectivity. The multiple merits of these cost-effective phenolic-resin-based carbons combined with a single-step and low-temperature preparation procedure reveal that they are excellent candidates for CO2 capture. Graphical abstract: Image 1